Third-order optical nonlinearity in silicon oxycarbide films - Yu, Xiuru; Yin, Luying; Lu, Heng; Huo, Yanyan; Jiang, Shouzhen; Zhao, Lina; Man, Baoyuan; Ning, Tingyin (Optical materials, 2020)
We study the third-order nonlinear optical properties of amorphous silicon oxycarbide (SiOxCy) films prepared by magnetron sputtering at room temperature and annealed in oxygen atmosphere at the temperature ranging from 200 °C to 600 °C. The third-order optical nonlinearity of the films was measured by Z-scan method at a wavelength of 1064 nm and a pulse duration 25 ps? The closed-aperture measurements show that the as-deposited films exhibit self-defocusing effect, while the annealed films present self-focusing behavior. The nonlinear refractive index is determined about |n2|~10−15 m2/W, which is four orders of magnitude larger than that of SiC crystals. The open-aperture results show that the as-deposited SiOxCy films and films annealed at 200 °C exhibit strong three-photon absorption behavior, while the SiOxCy films annealed at 400 °C and 600 °C exhibits nonlinear saturable absorption. The nonlinear absorption coefficients of films dependent on laser intensity are determined, and show saturable tendency. The results indicate that the third-order optical nonlinearity in SiOxCy films can be sensitively affected and tuned by the atom composition and microstructure, thus be of great significance for integrated nonlinear photonic devices. •The SiOxCy films without hydrogen were prepared using magnetron sputtering.•The nonlinear refractive index of SiOxCy films is determined about 10−15 m2/W.•The three-photon absorption and saturable absorption are found in SiOxCy films.•The atom composition and microstructure sensitively affected optical nonlinearity.